Bosnia and Herzegovina Diagnostic Review of Consumer Protection and Financial Literacy in Banking Services : Volume 2. Comparison with Good Practices - World Bank (World Bank, Washington, DC, 2017)
This diagnostic study exclusively covers consumer protection and financial literacy issues in the banking sector of Bosnia and Herzegovina (BiH). Household credit in BiH more than tripled in volume in 2003-2008, and in terms of GDP it expanded from 13 to 26 percent. Foreign currency loans represented 10 percent of GDP. Official statistics showed growth in the percentage of non-performing loans since 2007. To strengthen consumer protection in the banking sector in BiH, this review recommends measures in five key areas: legislative and institutional reform, consumer disclosure, business practices of banks, dispute resolution mechanisms, and financial education. The main tasks of this study have been: (1) to review the existing rules and practices in BiH compared to international good practices; (2) to provide recommendations on ways to improve consumer protection and financial capability; and (3) to refine a set of good practices prepared by the World Bank for assessing consumer protection in banking services, including financial capability. The Review is presented in two volumes: Volume I describes BiH Government policy for banking consumer protection, provides the banking sector statistics, and sets out the key findings and recommendations of the Review. Volume II provides an assessment of the BiH consumer protection institutional and legal framework and practices against the benchmark of Good Practices for the banking sector.